2017
DOI: 10.1515/jtes-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Job Dissatisfaction: Implications for Teacher Sustainability and Social Transformation

Abstract: Teachers play a key role in the social transformation agenda. This agentic position of the teacher implicates an agenda for sustainability programmes that position them for this complex responsibility. A qualitative case study research design was employed to obtain the perspectives of teachers on job dissatisfaction. The researchers followed a semi-structured interview approach to explore teachersí broader understanding on causes of job dissatisfaction among them. Data was interpreted through the narrative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
3
24
0
3
Order By: Relevance
“…Pressures emanating from society's perception of teaching career as however hindered both practicing teacher and student motivation to the profession [11]. Because of this, teachers may feel unappreciated and undervalued and may consider disengagement due to job dissatisfaction or forfeiting their job for something else [12,13].…”
Section: What Is Expected Of a Professional Teacher?mentioning
confidence: 99%
“…Pressures emanating from society's perception of teaching career as however hindered both practicing teacher and student motivation to the profession [11]. Because of this, teachers may feel unappreciated and undervalued and may consider disengagement due to job dissatisfaction or forfeiting their job for something else [12,13].…”
Section: What Is Expected Of a Professional Teacher?mentioning
confidence: 99%
“…Apart from dissatisfaction coming from managing and implementing the recent reform, OECD TALIS report (2013) showed that Italian teachers perceive their professional role as underestimated within the society. Recent studies showed that when teachers perceive poor social recognition, they are dissatisfied about their job [76].…”
Section: Similarities Between Teachers' Profilesmentioning
confidence: 99%
“…For instance, Okeke and Mtyuda (2017) have acknowledged that only 39 % of the teacher participants are efficient at disciplining students. Ortega and Fuentes (2015) have concluded that the quality of teaching depends on the quality of communication in the classroom.…”
Section: Discussionmentioning
confidence: 99%